Long-term efficacy and health consumption before and after ablation of AF. (3rd October 2022) - Englund, A; Tabrizi, F; Scheel, S
Abstract: Background: Atrial fibrillation (AF), the most common arrhythmia worldwide, is associated with increased morbidity and mortality. Catheter ablation of AF is the most effective treatment option for symptomatic patients. The long-term efficacy is however not very well studied nor is health consumption before and after an ablation of atrial fibrillation. Purpose: To study the long-term efficacy and health consumption before and after an ablation of AF in 1453 consecutive patients undergoing ablation in our institution. Methods: Consecutive patients undergoing radiofrequency ablation for AF were included prospectively. 4 mm irrigated ablation (Biosense Webster) catheters and Carto® were used for all procedures. After a mean period of 4 years a survey measuring arrhythmia symptoms was sent out to all patients who were treated with an ablation of AF between 1st of January 2010 and 31st of December 2016. Data was collected from local registries, the national registry for catheter ablations and the national health registry. Health consumption measured as in-hospital visits two years before and after the procedure was assessed. Results: 877 (72.7%) patients had no further symptomatic arrhythmia four years after the procedure. Among the 329 patients who still reported symptoms 237 (72%) had milder, 65 (20%) had unchanged and 20 (8%, 1.3% of total) had worsened symptoms after e ablation. The total number of in-hospital visits 2 years before and after the ablation was 4067. There were 2594 in-hospital visits before and 1473 after the ablation, a decrease by 43%. The majority of the these were arrhythmia related, 2264 and 908, respectively, a decrease by 60%. Seven patients had a stroke before the ablation and five after. The median length of stay was 1 day both before and after the ablation. Conclusion: Health consumption is significantly decreased after an ablation for AF. The long-term effect is good with freedom of symptomatic AF of approximately 70% after four years. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Biosense Webster Inc